Comparative analysis in shoreline changes in Kelantan, Malaysia using Digital Shoreline Analysis System (DSAS) / Muhammad Zakwan Anas Abd Wahid, Mohamed Syazwan Osman and Samsul Setumin - Abd Wahid, Muhammad Zakwan Anas; Osman, Mohamed Syazwan; Setumin, Samsul (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Kelantan is a Malaysian state renowned for its beautiful jungles and coastal districts. Kelantan, which is susceptible to monsoons and tidal waves, witnessed a tsunami-like inundation that affected its coastline landscape in 2014. This study does a comparative examination of shoreline alterations between 2013 and 2021 using the Digital Shoreline Analysis System (DSAS) technology. The coastline has grown by approximately 4.03 percent, from 62.1 kilometres to 64.6 kilometres, as a result of the implementation of digitalisation procedures. This highlights the increase in coastline areas between 2013 and 2021. Using GIS and satellite data, the study identifies considerable sedimentation in Pantai Geting and Lagun Jubakar, Tumpat, as well as severe erosion in Pantai Kundur and Pantai Cahaya Bulan, Kota Bharu. The analysis of the Shoreline Change Envelope (SCE) and Net Shoreline Movement (NSM) reveals an accretion rate of 728.44 m/year and a negative distance of -281.91 m/year, which indicates erosion. The paper concludes by emphasising Kelantan's shoreline expansion over the previous decade, stressing the significance of monitoring coastal changes for effective environmental management and catastrophe preparedness.